2011
DOI: 10.4168/aair.2011.3.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells and Allergic Diseases

Abstract: B cells are generally considered to positively regulate immune responses by producing antigen-specific antibodies. B cells are classified into classical CD5- conventional B cells and CD5+ B1 cells. The latter produce multi-specific autoantibodies and are thought to be involved in autoimmune diseases. However, evidence supporting a B cell negative regulatory function has accumulated over the past 30 years. Multiple reports have suggested that absence, or loss, of regulatory B cells exacerbates symptoms of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 76 publications
1
57
0
2
Order By: Relevance
“…17,19 With the ability to produce high levels of regulatory cytokines such as IL-10, B-1a cells are considered B cells with regulatory function. 33 We showed that B-1a cells were potent IL-10-producing cells at steady state when compared with the conventional B-2 subsets (Figure 4a). Moreover, B-1a cells interacted with CD4 1 T cells as APCs, leading to a larger amount of IL-10 production in in vitro cocultures (Figure 4b and c).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…17,19 With the ability to produce high levels of regulatory cytokines such as IL-10, B-1a cells are considered B cells with regulatory function. 33 We showed that B-1a cells were potent IL-10-producing cells at steady state when compared with the conventional B-2 subsets (Figure 4a). Moreover, B-1a cells interacted with CD4 1 T cells as APCs, leading to a larger amount of IL-10 production in in vitro cocultures (Figure 4b and c).…”
Section: Discussionmentioning
confidence: 86%
“…32 Among the diverse Treg populations, Tr1 cells specifically arise from naive precursors in the presence of IL-10. 33 Tr1 differentiation can be driven by immature or tolerogenic DCs through an IL-10-dependent mechanism or by self-APCpulsed antigens in the presence of IL-10. 17,19 With the ability to produce high levels of regulatory cytokines such as IL-10, B-1a cells are considered B cells with regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the capacity of Breg cells to suppress allergic airway inflammation seems to depend on the expression of CD1d, particularly in mice, but also presents an IL-10-dependent mechanism [7,[19][20][21]. Studies performed by van der Vlugt [16,22] have shown that schistosomes induce regulatory responses in both human and mouse CD1d hi B cells and that they can restore allergic inflammation by production of IL-10.…”
Section: Cd71mentioning
confidence: 99%
“…In food-allergic patients, the inhibitory role of IL-10-producing CD5 + B cells has been described [19]. Interesting results showing the clinical relevance of B reg cells were recorded in studies on specific oral immunotherapy protocols in patients with cow's milk allergy (CMA) [36].…”
Section: Food Allergymentioning
confidence: 99%
See 1 more Smart Citation